Instructional Design of English at Acceleration Program of SMP Negeri 1 Wonogiri: An Ethnographic Study - Sutrisno, Sutrisno; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Abdillah Nugroho, M. Hum (2015)
The objective of the research is to get a clear description of the instructional design of English at acceleration program of SMP Negeri 1 wonogiri in which covers about to know the syllabus used by the teachers, the objective of English teaching learning process, to know the materials, the classroom procedure, classroom activities, teacher's and learner's role, the media, and the evaluation. The research was conducted in Sekolah Menengah Pertama Negeri 1 Wonogiri, from August 2013 to October 2014. It is qualitative research in the form of ethnography study. The object of the research was the instructional design of English at acceleration program of SMP Negeri 1 Wonogiri. The data of this thesis were collected from several techniques including observation, interview, and document analysis. In analyzing the qualitative data, the researcher conducted method triangulation to examine the data from interview with the result of the observation, source triangulation to examine the information with the document, and the last is theory triangulation, it is to know the relation among the theories used in this research toward the data research. The efforts of study reveal an integrated syllabus which categorized into functional syllabus, text-based syllabus, and grammatical syllabus. The learning objectives are general and specific learning outcome. The instructional material is divided into text book, worksheet and hand out. The classroom procedure consisted of three stages namely exploration, elaboration, and confirmation. The classroom activities are oral repetition, identifying key words, answering questions, role play, problem solving, silent reading, questioning, skimming and scanning, constructing a new dialogue or conversation based on the example, and free writing. The media are LCD and tape recorder. The teacher's roles are motivator, guide, manager, explainer, and evaluator. The student's roles are participant, listener, evaluator, tutor for the other learners, and negotiator. The evaluation models are reviewing question, formative test, mid-test, summative test, and national examination. The research findings of this study imply that the instructional design of English at acceleration program of SMP Negeri 1 Wonogiri has been suitable with the theories of English teaching learning. Therefore, it is recommended that (1) the education stakeholders especially Dinas Pendidikan should give an addition of the frequency to conduct the seminars, trainings and also the short courses for all teachers, (2) School as the institution to conduct the teaching learning process should give the supervision directly to the educational practitioners, especially to the teachers, (3) The teachers should give much attention to method of teaching learning especially how to design the classroom activity, so the students will be highly motivated, the last (4) the other researchers develop some parts which have not been developed in this research.